2021
DOI: 10.1111/ppl.13510
|View full text |Cite
|
Sign up to set email alerts
|

Nonglandular prickle formation is associated with development and secondary metabolism‐related genes in Rosa multiflora

Abstract: Roses are among the most economically important ornamental plants worldwide. But prickles on the stem and leaves cause difficulties for cultivation or inconveniences during harvest and transportation, thus are an undesirable horticultural character. However, little is known about the molecular mechanisms of prickle development. In this study, we sought to develop Rosa multiflora (in the family Rosaceae) as a model plant to study prickle formation. The morphology, structure, and ontogeny of prickles were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…PCA analysis showed that the three replicate samples in each same group could be clustered together well, indicating that the accuracy of this sequencing result was high. Several notable developments and secondary metabolism-related TFs including NAC , TCP , MYB , homeobox , and WRKY were up-regulated in prickly internodes of Rosa multiflora [ 13 ]. A large number of TFs could be involved in the formation and development of trichomes, and the accumulation of Rosa sterilis RsETC1 ( R3-MYB ) was significantly higher in inflorescence stems compared with pedicels [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA analysis showed that the three replicate samples in each same group could be clustered together well, indicating that the accuracy of this sequencing result was high. Several notable developments and secondary metabolism-related TFs including NAC , TCP , MYB , homeobox , and WRKY were up-regulated in prickly internodes of Rosa multiflora [ 13 ]. A large number of TFs could be involved in the formation and development of trichomes, and the accumulation of Rosa sterilis RsETC1 ( R3-MYB ) was significantly higher in inflorescence stems compared with pedicels [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Lycium ruthenicum branch-thorns occur in response to drought and protect the corresponding axillary buds against drought stress [ 10 ]. Transcription factors such as MYB, bHLH, and TCP are involved in the development of prickles [ 11 , 12 , 13 ]. TCP TFs— THORN IDENTITY1 ( TI1 ) and TI2 , are expressed in axillary meristems and bind to the promoter of WUSCHEL, repressing the maintenance of cell proliferation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes expression profiling found that, PIN7 and LAX3 might be related with thorn phenotype of pummelo plant (Wu et al, 2021). Additionally, transcription factors such as TCP and NAC might regulate plant thorns development (Zhang et al, 2021; Zhang et al, 2021; Liu et al, 2023). With the increasing attention to the significant medicinal value of the Gleditsia , the molecular mechanism and gene regulation related to thorns development needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%